Síntese e caracterização de óxidos magnéticos diluídos nanoestruturados preparados por moagem mecânica - Campos Júnior, Luiz De Melo (2014)
The synthesis of nanostructured material trough new routes has conducted to materials with anisotropic shapes that would lead to new properties and applications. In this context, the aim of this work is to characterize structural and magnetically nanostructured Dilute Magnetic Oxides based on the ZnO matrix and doped with Co prepared by the mechanical milling process. The goal is to obtain nanocrystals of magnetic oxides without the observation of undesired secondary phases that would present a ferromagnetic order with Curie temperature above the room temperature. In order to evaluate the incorporation of Co in the ZnO host structure, it was performed a careful microstructural and chemical characterization using the following techniques: X-Ray Diffractometry, Scanning Electron Microscope, Energy Dispersive X-Ray Spectrometry, Raman Spectroscopy and X-Ray Absorption Near Edge Structure. The magnetic characterization was performed by SQUID magnetometry. Conjugating the results of different techniques, confirmed the replacement of Zn by Co in the structure of ZnO without significant distortion. We observed that the mechanical milling has an efficiency limit, which led us to reach median diameters for the milled grains of the order of 100 nm. We also observed that the mechanical milling process introduces structural defects in the ZnO:Co system in correlation with the mechanical milling efficiency. The SQUID magnetometry reveled the coexistence of paramagnetic and ferromagnetic phases. The analyses of the ferromagnetic phase showed clearly its intrinsic origin associated directly to the presence of the structural defects introduced by the mechanical milling.